Magic, Sheer Magic DVD review - Robertson, Allen (Dance Books Ltd., Alton,Hampshire (UK), 2006)
Review of the DVD of Mikhail Baryshnikov's The Nutcracker. PALABRAS CLAVE: Mikhail Baryshnikov, Gelsey Kirkland, The Nutcracker.
The Nutcracker, Kultur.